Indigenous women and traditional watercraft in native South America: paddling through gender prejudices - Saccone, Elena; Blasco, Jimena; Villarmarzo, Eugenia; Gianotti, Camila (Frontiers in Environmental Archaeology, 2026)
This article examines the roles of Indigenous women in navigation, watercraft, and aquatic lifeways across South America, challenging the masculine bias that has long shaped maritime archaeology and historical narratives. Drawing from a wide range of documentary, archaeological, and ethnographic sources, we adopt a feminist and decolonial framework to recover women's agency, technical knowledge, and symbolic presence in aquatic contexts. A reflexive methodology grounded in three principles (Aim, Attention, and Assessment) guided the identification, interpretation, and evaluation of evidence of women's participation in navigation. The dataset, encompassing diverse Indigenous groups and time periods, was systematized and mapped to reveal the spatial and temporal distribution of women's engagements with canoes and other traditional watercraft. The results demonstrate that women were central to aquatic life as paddlers, divers, steerswomen, and caretakers of canoes among peoples such as the Guató of the Pantanal, the Yagan and Kawesqar of Tierra del Fuego, and the Mapuche of southern Chile and Argentina, where canoes also appear in funerary contexts. In addition, iconographic and ethnographic materials from the Moche, Uros, Warrau, Emberá, and Tukano further attest to the enduring association between women and watercraft. Reinterpreting these records through a feminist and decolonial lens reveals that women's presence on the water was not an exception but integral to the social, economic, and cosmological fabric of their communities. Recognizing Indigenous women as navigators broadens the definition of maritime archaeology and contributes to the decolonization of its theoretical foundations, emphasizing navigation as a collective and gender-inclusive human practice.